2016
DOI: 10.1515/eces-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Use of Chemical Transformation Modules in Calpuff on the Results of Air Dispersion Modelling

Abstract: Assessment of the impact on air quality for combustion sources should be carried out using advanced modelling systems with chemical transformation modules taken into account, especially for the facilities characterized by significant emission of gaseous air pollutants (including SO2). This approach increases the reliability of the obtained evaluation results by modelling the formation of secondary inorganic aerosol (SIA) in the air which can substantially contribute to PM10. This paper assesses in this regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To identify whether the ammonia is sufficient, the ammonium-to-sulfate ratio (Ratio A-to-S ) is calculated with the published data as well. It is reported that the North China Plain experienced ammonia insufficiency during summer (Ratio A-to-S : less than 1.5), limiting the formation and partitioning of nitrate into the particle phase (Pathak et al, 2004(Pathak et al, , 2009(Pathak et al, , 2011. However, Ratio A-to-S in Beijing during winter was always above 1.5.…”
Section: Comparison Of Major Inorganic Compositions During the Early mentioning
confidence: 99%
“…To identify whether the ammonia is sufficient, the ammonium-to-sulfate ratio (Ratio A-to-S ) is calculated with the published data as well. It is reported that the North China Plain experienced ammonia insufficiency during summer (Ratio A-to-S : less than 1.5), limiting the formation and partitioning of nitrate into the particle phase (Pathak et al, 2004(Pathak et al, , 2009(Pathak et al, , 2011. However, Ratio A-to-S in Beijing during winter was always above 1.5.…”
Section: Comparison Of Major Inorganic Compositions During the Early mentioning
confidence: 99%
“…Particle acidity has widely been studied due to its important roles in haze formation, and is widely implemented in major models (Yu et al, 2005;Robert et al, 2016). Since there was rarely practical method to direct measure the acidity of particles in real atmosphere (Wei et al, 2018;Freedman et al, 2019), calculation of the particle pH by thermodynamic models had been the most used method to quantify particle acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Poor air quality in Krakow, often observed during the heating season, is usually associated with unfavorable synoptic-scale (anti-cyclonic circulation), low temperature, low mixing-layer height and low wind speed, which hinders the dispersion of pollutants in the air [58,60,61,64,65], and in the case of fine solid particles with increased formation of secondary inorganic (SIA) or organic (SOA) aerosols [62,[68][69][70][71] and a large inflow background of dust pollution from adjacent areas [22,24,65,67]. Despite a significant reduction of SIA precursor emissions from large combustion plants (SO 2 and NO x ) and residential heating (SO 2 ), the contribution of SIA formation in fine particulate matter is now much greater [68][69][70] than it has been reported for several years ago [72,73]; this indicates an increase in the role of NO x (derived from combustion processes, including to a large extent from the combustion of engine fuels) in the formation of SIA, and thus their greater impact on the levels of fine particulate matter in the air [91,92,97].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many other studies present long-term trends in changes of air pollutants concentrations in Krakow and their impact on health [74][75][76][77][78][79][80][81][82], the mineralogical composition and microbiological characteristics of aerosols [83,84], the oxidative potential of PM 10 and PM 2.5 [85], the chemical composition of street dust [86] and dry and wet deposition [87][88][89]. The results of measurements from the automatic air quality monitoring station in Krakow were also used to prepare the pollution background necessary in the process of air pollution modeling and the assessment or validation of the dispersion [90][91][92][93][94][95][96][97] or prognostic [98][99][100][101] models used.…”
Section: Introductionmentioning
confidence: 99%